Alley farming - Kang, B.T.; Atta-Krah, A.N.; Reynolds, L. (Technical Centre for Agricultural and Rural Cooperation, 1999)
The widespread adoption of alley farming – an important farming and land-use system – could reduce the threat to the word’s remaining tropical forests and transform the prospects for sustainable agriculture in the fragile lowland tropics. This concise, practical booklet covers the development of alley farming, provides practical guidelines for establishing and managing it, and outlines the benefits to crop and livestock production and other by-products. Helpfully illustrated with photographs and diagrams, the text should encourage the wider use of this adaptable, sustainable farming technique.